Rotten Ralph - Gantos, Jack.; Rubel, Nicloe (Boston : Houghton Mifflin, 1976)
Sarah's difficult cat, Ralph, mends his ways after she sends him to a feline finishing school, but his current change in behavior may not reflect a permanent change of heart.
3.4
K-3
K-3.
Wilson's Children
Elem. School Library Collection
School Library Journal
Keywords: Behavior -- Fiction; Circus -- Fiction; Cats -- Fiction; Human behavior -- Fiction; Circus -- Fiction; Cats -- Fiction